Esquema de comunicação MIMO para quatro antenas transmissoras e taxa de transmissão unitária: análise de desempenho e de robustez - Valduga, Samuel Tumelero (2014)
In this master thesis it is proposed a MIMO communication scheme with four transmit antennas and unitary transmission rate. The performance and robustness of the scheme are evaluated and compared with other good proposals recently presented in the literature. The proposed scheme uses a preprocessor based on phase feedback. The preprocessor allows the proposed scheme to obtain full diversity and also coding gain. The pre-processing considers a codebook design, whose size is dependent on the number of feedback bits. Error probability analysis is provided, where the upper and lower bounds for different numbers of feedback bits and antennas are presented, considering two different types of constellations, QAM and PSK. For robustness analysis, channels estimators were used. For the channel estimators model it was added the effects of spatial correlation, enabling the evaluation the losses caused by the spatial correlation among the antennas, and the Doppler effect, for evaluating the loss performance due to the relative mobilitys between trnamitter and receiver.